Anxiolytic activity of a Boophone disticha: Behavioral analysis in mice subjected to early maternal separation followed by later stressors: paper presented at the International summit on past and present research systems of green chemistry;August 25-27, 2014 Hilton Philadelphia Airport, USA - Pote, William; Chinyanga, Herbert M.; Musara, Colin; Pfukenyi, Davies; Gadaga, Louis L.; Nyandoro, George; Tagwireyi, Dexter (SciTechnol, 2016)
Paper presented at the International summit on past and present research systems of green chemistry;August 25-27, 2014 Hilton Philadelphia Airport, USA